Synthesis Of Cs-Pollucite Nanozeolite And Catalytic Study In Base-Catalyzed Benzaldehyde Condensation Reactions - Aleid, Ghadah Mohammad S. (2020)
This project aims to synthesize nanosized Cs-pollucite (ANA topology) solid catalyst without organic structure-directing agent for condensation reactions of benzaldehydes. The first part focuses on the effect of the synthesis parameters (e.g. heating temperature, and hydrogel chemical composition) on the crystallization process of nanosized Cs-pollucite zeolites.